tif-1 mutation alters polynucleotide recognition by the recA protein of Escherichia coli. - McEntee, K (1981)
The requirements for polynucleotide-dependent hydrolysis of ATP and for proteolytic cleavage of phage lambda repressor have been examined for both the wild-type (recA+ protein) and the tif-1 mutant form [tif(recA) protein] of the recA gene product. The recA+ and tif(recA) proteins catalyze both reactions in the presence of long single-stranded DNAs or certain deoxyhomopolymers. However, short oligonucleotides [(dT)12, (dA)14] stimulate neither the protease nor the ATPase activities of the recA+ protein. In contrast, these short oligonucleotides activate tif(recA) protein to cleave lambda repressor without stimulating its ATPase activity. Moreover, both the ATPase and protease activities of the tif(recA) protein are stimulated by poly(rU) and poly(rC) whereas the recA+ protein does not respond to these ribopolymers. We have purified the recA protein from a strain in which the tif mutation is intragenically suppressed. This mutant protein (recA629) is inactive in the presence of (dT)12, (dA)14, poly(rU), and poly(rC) for lambda repressor cleavage and ATP hydrolysis. These results argue that the tif-1 mutation (or mutations) alters the DNA binding site of the recA protein. We suggest that in vivo the tif(recA) protein is activated for cleaving repressors of SOS genes by complex formation with short single-stranded regions or gaps that normally occur near the growing fork of replicating chromosomes and are too short for activating the recA+ enzyme. This mechanism can account for the expression of SOS functions in the absence of DNA damage in tif mutant strains.